The determinants of strikes in the Mexican automobile industry, 1980–2012. (3rd September 2018) - Tuman, John P.
Abstract : This study examines the variation in the number of strikes, and days lost to strikes, in the Mexican automobile industry. The analysis draws on an original data set on strikes in 11 Mexican finished vehicle plants for the period of 1980 and 2012. The statistical models are estimated using pooled Poisson and negative binomial regression. The findings of the study provide empirical support for perspectives that emphasize the legacies of state corporatism, and theories that focus on the effects of regional integration. Unions that were independent from the Confederation of Mexican Workers, and democratic unions, were associated with a higher count of strikes, and strikes of longer duration in each plant. Higher tariffs on imported vehicles also had a positive effect on strikes. However, the ratio of exports to national production in each firm was associated with a reduction in the number and duration of strikes. After adjusting for these influences, lagged real wage changes in each plant, local unemployment rates, and other factors had no influence.